The Effect Of Digital Transformation And Knowledge Sharing On Employee Performance By Mediating Organizational Commitment At The Land Office In East Nusa Tenggara Province - Novan Triswandana; Sarwo Edy Handoyo; Ikhwan HS (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Digital transformation has become an urgent necessity for modern organizations, including higher education institutions, to enhance employee performance in the face of increasingly competitive work environments. This process relies not only on the adoption of technology but also on the ability of individuals to effectively engage in knowledge sharing. This study aims to analyze the effect of digital transformation and knowledge sharing on employee performance, with organizational commitment as a mediating variable. A quantitative approach was employed, using Partial Least Square-Structural Equation Modeling (PLS-SEM) on a sample of employees within a university setting. The results indicate that digital transformation has a significant positive effect on employee performance, both directly and indirectly through organizational commitment. Knowledge sharing was also found to play a crucial role in improving performance, with organizational commitment serving as a mediator that strengthens this relationship.